Blood glucose control and compliance of diabetic children - F. P. R. de Villiers; E. Chester; K. E. C. Meyers (AOSIS, 1997)
Non-compliance is an important factor hindering good control in diabetics. The aim of this study was to identify areas of poor compliance with the diabetes management regimen in the children attending our clinic. A questionnaire was administered to 57 patients who attend the Paediatric Diabetes Clinic. It was designed to elicit socio-demographic data and information about the diabetic regimen. Prior to the administration of the questionnaire, patients were classified as being well, satisfactorily or poorly controlled, based on their average glycosylated Haemoglobin results over the past year.